VExUS in the Management of Constrictive Pericarditis: A Case Report. - Abu-Naeima, Eslam (2023)
We present the case of a patient admitted to the intensivecare unit with hypoxia and renal failure one month followingpericardiectomy for constrictive pericarditis with a post-operative course complicated by oscillating renal dysfunction. The use of point of care ultrasound and particularly venous Doppler indices allowed the treating team to identify physiological disturbances and optimize management. This case illustrates how bedside analysis of physiopathology can demystify the relationship between fluid management and renal dysfunction which can be a challenge to accurately identify without the tools to assess venous congestion.